Institutional analysis of management and outcome of Chronic Subdural Hematoma in elderly population (Nepal Journal of Neuroscience, 2023)
The elderly population is particularly at risk for developing Chronic Subdural hematomas (CSDH) as a result of trivial trauma. This,  along with the inevitable associated medical co-morbidities, manifests as a challenge for surgical management. The outcomes therefore can sometimes be unfavourable, leading to significant burden on the lives of patients, their families as well as the healthcare set-ups around the world. This seemingly innocuous disease entity can cause poor outcomes in terms of morbidity and mortality for this particular population. Despite having multiple treatment options, both surgical and medical, no consensus has been reached regarding optimal management strategies. We present this article to analyse the management and outcomes as well as challenges faced in the elderly population with CSDH reporting to a tertiary care neurosurgical centre.